Biocatalysis Based on Heme Peroxidases Peroxidases as Potential Industrial Biocatalysts - Torres, Eduardo; Ayala, Marcela; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
This monograph describes many applications of peroxidase-based biocatalysis in the biotechnology industry. The need for such a book emerges from the considerable amount of new data regarding the phylogeny, reaction mechanisms, thermodynamic characterization and structural features of fungal and plant heme peroxidases that has been generated in the past 10 years, since the last specialized book on peroxidases was published. The aim of this book is to present recent advances on such basic aspects as evolution, structure-function relation and catalytic mechanism as well as applied aspects, such as bioreactor and protein engineering, to provide the tools for rational design of enhanced biocatalysts and biocatalytic processes.
Molecular and Structural Aspects of Peroxidases -- Molecular Phylogeny of Heme Peroxidases -- Structural and Functional Features of Peroxidases with a Potential as Industrial Biocatalysts -- Redox Potential of Peroxidases -- Catalytic Mechanisms of Heme Peroxidases -- Prospective Usage of Peroxidases in Industry -- Potential Applications of Peroxidases in the Fine Chemical Industries -- Grafting of Functional Molecules: Insights into Peroxidase-Derived Materials -- Applications and Prospective of Peroxidase Biocatalysis in the Environmental Field -- Challenges in the Application of Peroxidases -- Enzyme Technology of Peroxidases: Immobilization, Chemical and Genetic Modification -- Reactor Engineering -- Deactivation of Hemeperoxidases by Hydrogen Peroxide: Focus on Compound III -- Heterologous Expression of Peroxidases -- A Compendium of Bio–Physical–Chemical Properties of Peroxidases.
Keywords: Biotechnology; Enzymology; Physical chemistry; Biotechnology; Enzymology; Physical Chemistry